Körper in biografieanalytischer Perspektive Zum Verhältnis von Körper, Biografie und ihrer Erforschbarkeit - Gabriel, Sabine (Qualitative Fall- und Prozessanalysen. Biographie - Interaktion - soziale Welten, 2021)
How does body knowledge develop? How does it influence one's own actions and experiences? This book offers a first attempt to classify the relations of body and biographical process experience. For this purpose, narrative interviews with professional dance practitioners were evaluated with a modified social science process analysis, for which a 'lived body heuristic' was developed. The 'lived body heuristic' opens up fundamental research-practical connections.